R&D investment and political connections - complements or substitutes? evidence from Russia - Natalia Lamberova (Baltic Journal of Economics)
Technological progress is an important factor in economic development, yet it can create problems for governments, if the costs are felt by their supporters while the benefits go to potential challengers. As a result, politicians face a trade-off between stifling economic growth and facing the threat of technological displacement of their supporters. This paper proposes a model of government support for innovation that preserves technological advantage of companies connected to the incumbent. Provided the government values the future higher than the companies, it can stimulate the development of new technologies by both connected and unconnected companies via co-funding the costs of innovation. In addition, it can condition the provision of additional benefits received by the connected companies on the success of their research and development (R&D) project, stimulating extra effort on their part. This model implies three observable implications: governments will distribute cost-reducing grants to both connected and unconnected companies; connected companies will show a larger effect of R&D grant support on economic performance; and during the assessment period of R&D projects, government contracts will preferentially support connected companies. Analyzing evidence from a cost-reducing R&D support program in Russia, a trajectory-balancing approach produces results consistent with each of these implications.